Sistem Tutorial Berintelegensia Pengambilan Keputusan Perbaikan Harddisk - Agusta Rakhmat Taufani; Irawan Dwi Wahyono (SMATIKA JURNAL, 2019)
Hard disk is a popular storage media used by users because its characteristics are durable and easy to use. Even though it has come out of a new storage device such as Solid-State Drive (SSD), hard drives are still more popular in usability because of their ergonomic factors. Like other devices, hard disks are also vulnerable to damage caused by various factors. Proper handling of the damage must be based on valid knowledge and can be accessed easily. Therefore, it is necessary to develop a system of repair tutors specifically dealing with damage, especially hard disk devices as a user decision-making tool in the process of repairing these devices utilizing artificial intelligence. The decision-making strategy used uses the certainty factor method based on certainty. After going through the equivalence partitioning testing process, in general this system produces a total percentage of 100% on the success of the system item test in the testing process of the 25 items tested. Thus, the system is running according to the design of the prototype.